The value of x = 16, y = 172 and z = 2.
x - 4z = 12x - y - 6z = 42x + 3y - 2z = 8
let x - 4z = 8 be equation (1), 12x - y - 6z = 8 be equation (2) and 42x + 3y - 2z = 8 be equation (3)
x - 4z = 8
x = 8 + 4z
12x - y - 6z = 8
12(8 + 4z) -y - 6z =8
96 + 48z - y - 6z = 8
42z - y = -88
y = 42z + 88
42x + 3y - 2z = 8
42(8+4z) + 3(42z + 88) - 2z = 8
336 + 168z + 126z + 264 - 2z = 8
168z + 126z + 2z = 336+264 - 8
296z= 592
z = 2
substituting the value of z
x = 8 + 4z
= 8 + 4(2)
8+8 = 16
y = 42z + 88
42(2) + 88
84 + 88= 172
The value of x = 16, y = 172 and z = 2.
To learn more about algebraic equation refer here
https://brainly.com/question/13729904
#SPJ9